Freeze-Dried Clopidogrel Loaded Lyotropic Liquid Crystal: Box-Behnken Optimization, In-Vitro and In-Vivo Evaluation - Hakeem, Eman A.; El-Mahrouk, Galal M.; Abdelbary, Ghada; Teaima, Mahmoud H. (Current Drug Delivery, 2020)
Background: Clopidogrel (CLP) suffers from extensive first pass metabolism results in a negative impact on its oral systemic bioavailability. Cubosomes are Lyotropic Liquid Crystalline (LLC) nano-systems comprising monoolein, a steric stabilizer and an aqueous system, it considered a promising carrier for different pharmaceutical compounds. Box-Behnken Design (BBD) is an efficient tool for process analysis and optimization skipping forceful treatment combinations. Objective: The study was designed to develop freeze-dried clopidogrel loaded LLC (cubosomes) for enhancement of its oral bioavailability. Methods: A 33 BBD was adopted, the studied independent factors were glyceryl monooleate (GMO lipid phase), Pluronic F127 (PL F127steric stabilizer) and polyvinyl alcohol powder (stabilizer). Particle Size (PS), Polydispersity Index (PDI) and Zeta Potential (ZP) were set as independent response variables. Seventeen formulae were prepared in accordance with the bottom up approach and in-vitro evaluated regarding PS, PDI and ZP. Statistical analysis and optimization were achieved using design expert software®, then the optimum suggested formula was prepared, in-vitro revaluated, freeze-dried with 3% mannitol (cryoprotectant), solid state characterized and finally packed in hard gelatin capsule for comparative in-vitro release and in-vivo evaluation to Plavix®. Results: Results of statistical analysis of each individual response revealed a quadratic model for PS and PDI where a linear model for ZP. The optimum suggested formula with desirability factor equal 0.990 consisting of (200 mg GMO, 78.15 mg PL F127 and 2% PVA). LC/MS/MS study confirmed significant higher Cmax, AUC0-24h and AUC0-∞ than that of Plavix®. Conclusion: The results confirm the capability of developed carrier to overcome the low oral bioavailability.
Keywords: Clopidogrel